Analysing the Hidden Mass Boson - Mikhail Jakovlevich Ivanov; Vadim Konstantinovich Mamaev (Physics of Entropy, Radiation and Gravitating Matter with Examples of General and Analytical Solutions, 2021)
The proof for the existence of the hidden mass boson is presented using observational data from modern physics and based on the fruitful theories of M. Planck and A. Einstein. The key parameters of this mass particle are predicted in this article, as well as its potential structure. Furthermore, the spread system of Maxwell linear equations and the close system of nonlinear conservative equations are written in the context of the phenomenological definition of the hidden mass continuous medium. Our paper accurately describes the displacement current, the Umov-Pointing vector, and physical vacuum polarization. We discuss some applications of our methodology for simulations of nature and technical device processes. Numerical solutions for cosmic jets and air breathing engines are shown in particular.